THE IMPROVEMENT OF EMPLOYEE PERFORMANCE THROUGH EMPLOYEE COMPETENCE, WORK FACILITIES, WORK DISCIPLINE, AND ORGANIZATIONAL COMMUNICATION - Nurul Huda Agustiani; Ismiyati, Ismiyati; Mar’atus Sholikah; Holy Latifah Hanum; Dian Fithra Permana (Jurnal Ekonomi, 2023)
This study aims to determine what factors affect the performance of employees at the Finance Department of Universitas Negeri Semarang (Unnes). This type of research is quantitative research. The population in this study were all employees of the Finance Section of Unnes, amounting to 75 people. The sampling technique carried out in this study uses probability sampling with a proportional random sampling technique. The number of samples was determined using the Slovin formula with 63 people. The method of collecting data is the questionnaire method. The data analysis method used is multiple regression analysis. The analysis results show that the factors that influence employee performance are employee competence, work discipline, organizational communication, and work facilities. These variables have a significant value of less than 0.05, which is 0.000. For this reason, the four variables proved to affect employee performance significantly. Of the four variables, the organizational communication variable occupies the lowest position, so for employee performance to increase in the Finance section of Unnes, employees are expected to communicate well with superiors or other employees.